Optimal Design of Double-stage Wheel Hub Reducer System based on Fuzzy Theory - Xiong Yong (Jixie chuandong)
The planetary wheel hub reducer has the advantages of compact structure,high bearing capacity and large transmission ratio,which is widely used in heavy duty truck. According to the structural characteristics of double-stage planetary wheel hub reducer system,the double-stage wheel hub reducer is designed based on the fuzzy reliability optimization design with the multi-objects. The first-level objective function is the minimal volume,the second-level objective function is the greatest reliability. Based on the characteristic of genetic algorithms,improving the weight coefficients of the search methods and increasing the optimization searching space,compared with other optimization methods,the result is improved. Based on the results,the fuzzy theory is applied to the Taguchi method. The robust design of double-stage wheel hub reducer is carried out. The results of robust design are compared with the above results. According to the optimal design results,the simulation analysis of main components,gear,bearings of the double-stage wheel hub reducer system is carried out. The simulation result met the design requirements,which verified the feasibility of the optimized design.